Glenn Gould and ‘Opus 2’: An outline for a musical understanding of contrapuntal radio with respect to The Idea of North - Cushing, Anthony (Circuit, 2012)
The Idea of North is the first of Glenn Gould’s Solitude Trilogy documentaries. Like the two works that follow it in the trilogy, North attracts a significant amount of attention for its place in a nether region between Gould as a performer and Gould the intellectual. The bulk of the literature on the work debates categorizing it as documentary, radio drama/theatre, or music. Gould’s own descriptions of it encompass all three and render the task of pigeonholing the work difficult. This article will explore what makes The Idea of North musical. I contend that, even if considered as documentary, drama, or music, the work is musically conceived and musical and, as such, is a milestone for Gould in developing his compositional voice.